Bta-miR-665 improves bovine blastocyst development through its influence on microtubule dynamics and apoptosis - Guan, Xuefeng; Fan, Yuan; Six, Rani; Benedetti, Camilla; Raes, Annelies; Fernandez Montoro, Andrea; Cui, Xiaole; Azari Dolatabad, Nima; Van Soom, Ann; Pavani, Krishna Chaitanya; Peelman, Luc (Frontiers in Genetics, 2024)
Extracellular vesicles (EVs) contain microRNAs (miRNAs), which are important regulators of embryonic development. Nevertheless, little is known about the precise molecular processes controlling blastocyst development and quality. In a previous study, we identified bta-miR-665 as one of the miRNAs more abundantly present in extracellular vesicles of embryo-conditioned culture media of blastocysts compared to degenerate ones. Here, we investigated the effect and regulatory roles of bta-miR-665 in blastocyst development by supplementation of bta-miR-665 mimics or inhibitors to the culture media. Supplementation of bta-miR-665 mimics improved cleavage and blastocyst rate (P < 0.01), and blastocyst quality as indicated by increased inner cell mass rates and reduced apoptotic cell ratios (P < 0.01). Furthermore, supplementation of bta-miR-665 inhibitors had the opposite effect on these phenotypes. Low input transcriptome analysis and RT-qPCR revealed that bta-miR-665 acts on genes linked to microtubule formation and apoptosis/cell proliferation. These insights not only elucidate the important role of bta-miR-665 in embryo development, but also underscore its potential in improving reproductive efficiency in bovine embryo culture.